Robert Browning and Mick Imlah: Forming and Collecting the Dramatic Monologue - Morton, John (Australasian Journal of Victorian Studies, 2013)
This article considers the history of the dramatic monologue with a focus on the neo-Victorian poetry of Mick Imlah (1958-2009). Beginning by identifying the inherent strangeness of the monologue form by looking at the ongoing debates on the relationship between these poems, and their speakers, readers and authors, it initially focuses on Browning’s monologues, and the tension between “democracy” and “difficulty” therein. It moves on to offer a brief history of the dramatic monologue in the twentieth century, focusing on Anthony Thwaite’s 1980 collection Victorian Voices which is an attempt, following Browning’s model, of rehabilitating the historically dispossessed through a collection of “voices” in blank verse. The main focus of the article is Mick Imlah’s poetry, not least his innovations in neo-Victorian poetry in both the dramatic monologue form and other modes of writing, linking them to recent theoretical works on the neo-Victorian. The article goes on to consider his later development of a more expansive approach to the dramatic monologue through the topic of Scottish history. The polyphonic history Imlah creates in the meticulously-constructed collection The Lost Leader means that, through its fashioning, it is a culturally-specific, if at times irreverent, inheritor to Men and Women.